Re-energizing the Corporation : How Leaders Make Change Happen. - Ridderstrale, Jonas (John Wiley & Sons, 2008)
Re-energizing The Corporation is built on the groundbreaking 3e leadership model which makes sense of the three Es of Envisioning, Engaging and Executing. By understanding and following the model, you will be able to create compelling pictures of the future of your organization; build a following of individuals committed to getting the vision into reality; and maximize team performance to deliver on your dream.